PENGARUH CELEBRITY ENDORSER DAN ELECTRONIC WORD OF MOUTH TERHADAP MINAT BELI MADAME GIE DENGAN BRAND IMAGE SEBAGAI VARIABEL INTERVENING DI KOTA MATARAM - Sella Fatra Laili Kamalin; Zulkarnaen, Zulkarnaen (Jurnal Cakrawala Ilmiah, 2025)
This study aims to test the influence of Celebrity Endorser and Electronic Word of Mouth on buying interest in Madame Gie skincare with Brand Image as an Intervening variable in the city of Mataram. The population of this study is domiciled in the city of Mataram. The sampling technique, non-probability sampling using the lemeshow formula became 97 respondents. This research was carried out by distributing questionnaires, using the regression path analysis method of models 1 and 2. The results of the study show that: (1) Celebrity Endorser has a significant effect on Brand Image, t count 4.128 > t table 1.9855. (2) Electronic Word of Mouth has a significant effect on Brand Image, t count 3.889 > t table 1.9855. (3) Celebrity Endorser has a significant effect on Buying Interest, t count 2.734 > t table 1.9858. (4) Electronic Word of Mouth has a significant effect on Buying Interest, t count 2.348 > t table 1.9858. (5) Brand Image has a significant effect on buying interest, t count 2, 348 > t table 1.9858. (6) Celebrity Endorser has a significant effect on Buying Interest through Brand Image, Z calculates 2.06856415 > a value of 1.98 and p value 0.0385870 < a value of 0.05. (7) Electronic Word of Mouth has a significant effect on Buying Interest through Brand Image, Z calculates 2.03512643 > a value of 1.98 and a p value of 0.04183815 < a value of 0.05.